My Friend Fear: Finding Magic in the Unknown - Meera Lee Patel (Particular Books, 2018)
"From the bestselling author of Start Where You Are comes a vibrantly inspiring look at making peace with fear--to become our truest selves On the heels of her bestselling journal Start Where You Are, author and illustrator Meera Lee Patel takes us deeper into her artistic vision and emotional journey in this stunning new four-color book. A mix of personal reflections, inspirational quotes, questions for reflection, and breathtaking watercolor visuals, My Friend Fear asserts that having big fear is an opportunity to make big changes, to discover the remarkable potential inside ourselves"-- Provided by publisher. "From the bestselling author of Start Where You Are comes a vibrantly inspiring look at making peace with fear--to become our truest selves On the heels of her bestselling journal Start Where You Are, author and illustrator Meera Lee Patel takes us deeper into her artistic vision and emotional journey in this stunning new four-color book. A mix of personal reflections, inspirational quotes, questions for reflection, and breathtaking watercolor visuals, My Friend Fear asserts that having big fear is an opportunity to make big changes, to discover the remarkable potential inside ourselves"-- Provided by publisher.